Development of a Web-based Library Information System Integrated with a Webcam-based Barcode Scanner - Nabilah Lestari; Ahmad Fauzi (Universitas Islam Indragiri, 2026)
The process of borrowing and returning books in some school libraries is still carried out manually, resulting in slower service times and a higher risk of data recording errors. Therefore, a library information system is needed to improve transaction efficiency and data management accuracy. This study aims to develop a web-based library information system integrated with a webcam-based barcode scanning feature, eliminating the need for additional scanning devices. The research employs a Research and Development (R&D) approach using the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. System evaluation was conducted using Black Box Testing, transaction time efficiency analysis, data accuracy measurement, assessment of lighting intensity on webcam-based barcode scanning performance, and usability testing using the System Usability Scale (SUS). The results indicate that all system functions operate properly. The system reduces the average transaction time from 72.06 seconds to 24.48 seconds (66% efficiency improvement) and increases data recording accuracy from 60% to 100%. Webcam-based barcode scanning performs optimally under lighting conditions of ≥150 lux. The usability evaluation achieved a SUS score of 85.8 (excellent). However, system performance is still influenced by lighting conditions and camera quality. Future research may focus on enhancing the system by incorporating image processing techniques or alternative identification technologies to further improve scanning accuracy.